2021
DOI: 10.1002/er.6757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gas purging on the performance of a proton exchange membrane fuel cell with dead‐ended anode and cathode

Abstract: Water management is an important issue to be addressed to maintain the stable and efficient operation of a proton exchange membrane fuel cell (PEMFC).Gas purging is commonly performed to remove accumulated water in a PEMFC, especially in a dead-ended fuel cell system. A 3D dynamic model with a user-defined inlet boundary condition is proposed to study the effect of gas purging with different purge durations in an H 2 /O 2 PEMFC. The results show that the performance immediately deteriorates and then recovers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Steinberger et al 42 studied the purge methods with a nitrogen content of 10% and 30%, and the discontinuous and continuous purge methods were used to improve the utilization rate of hydrogen. Shen et al 43 have shown that purge strategies are directly related to fuel cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…Steinberger et al 42 studied the purge methods with a nitrogen content of 10% and 30%, and the discontinuous and continuous purge methods were used to improve the utilization rate of hydrogen. Shen et al 43 have shown that purge strategies are directly related to fuel cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Due to its high energy conversion efficiency, low noise, and environment friendly, it is known as the most promising power sources in the 21st century. 3 Through the development of PEMFC technology, fuel cell vehicles (FCVs) have made considerable progress in the international market. Many FCVs produced by many companies such as Honda, Toyota, Hyundai, and General Motors have been demonstrated and sold on a small scale around the world.…”
Section: Introductionmentioning
confidence: 99%
“…1 Proton-exchange membrane fuel cell (PEMFC) has been considered as a potential power supply system, due to its environment-friendly adaptability, and high efficiency in directly converting the chemical energy stored in the fuel and oxidant into electricity. 2,3 PEMFCs have rapidly developed over decades of research, but water and thermal management remain as major obstacles in its commercialization, specifically in a complicated system. 4 Thermal management is a significant issue in promoting the reliability and durability of a PEMFC.…”
Section: Introductionmentioning
confidence: 99%